Experimental colitis in IL-10-deficient mice ameliorates in the absence of PTPN22. (10th July 2019) - Jofra, T; Galvani, G; Cosorich, I; De Giorgi, L; Annoni, A; Vecchione, A; Sorini, C; Falcone, M; Fousteri, G
Summary: Interleukin (IL)-10 plays a key role in controlling intestinal inflammation. IL-10 -deficient mice and patients with mutations in IL-10 or its receptor, IL-10R, show increased susceptibility to inflammatory bowel diseases (IBD). Protein tyrosine phosphatase, non-receptor type 22 (PTPN22) controls immune cell activation and the equilibrium between regulatory and effector T cells, playing an important role in controlling immune homoeostasis of the gut. Here, we examined the role of PTPN22 in intestinal inflammation of IL-10 -deficient ( IL-10 –/– ) mice. We crossed IL-10 –/– mice with PTPN22 –/– mice to generate PTPN22 –/– IL-10 –/– double knock-out mice and induced colitis with dextran sodium sulphate (DSS). In line with previous reports, DSS-induced acute and chronic colitis was exacerbated in IL-10 –/– mice compared to wild-type (WT) controls. However, PTPN22 –/– IL-10 –/– double knock-out mice developed milder disease compared to IL-10 –/– mice. IL-17-promoting innate cytokines and T helper type 17 (Th17) cells were markedly increased in PTPN22 –/– IL-10 –/– mice, but did not provide a protctive function. CXCL1/KC was also increased in PTPN22 –/– IL-10 –/– mice, but therapeutic injection of CXCL1/KC in IL-10 –/– mice did not ameliorate colitis. These results show that PTPN22 promotes intestinal inflammation in IL-10 -deficient mice, suggesting that therapeutic targeting of PTPN22 might be beneficial in patients with IBD and mutations in IL-10 and IL-10R . Graphical Abstract: